Gnostic countercultures: terror and intrigue - De Conick, April D.; Roig Lanzillotta, Lautaro (Brill, 2020)
"In Gnostic Countercultures, fourteen scholars investigate countercultural aspects associated with the gnostic which is broadly conceived with reference to the claim to have special knowledge of the divine, which either transcends or transgresses conventional religious knowledge. The papers explore the concept of the gnostic in Western culture from the ancient world to the modern New Age. Contributors trace the emergence, persistence, and disappearance of gnostic religious currents that are perceived to be countercultural, inverted, transgressive and/or subversive in their relationship to conventional religions and their claims to knowledge. The essays represent a selection of the papers delivered at the international congress Gnostic Countercultures: Terror and Intrigue convened at Rice University, March 26-28, 2015. The essays were originally published in Gnosis 1.1-2 (2016) and are available for the first time under separate cover"